Spiritual orientation and mental health: an SEM analysis of meaning and death attitudes as mediators in Turkish religious officials - Soylev, Omer Faruk; Kaya, Cinar; Okan, Nesrullah (Springernature, 2025)
This study examines the relationships between spiritual orientation, meaning in life, attitudes towards death, and indicators of psychological health (depression, anxiety, and stress) among 348 Muslim religious officials in Turkey (28% female). Using structural equation modelling (SEM), the results showed that spiritual orientation directly and indirectly reduces psychological distress by enhancing personal meaning and fostering more accepting attitudes towards death. Results showed a moderate positive association between spiritual orientation and meaning in life, and weak but significant negative associations between meaning/attitudes towards death and psychological symptoms. As one of the first empirical studies to examine the mediating role of death attitudes in this population, the research highlights the theoretical relevance of existential frameworks such as logotherapy. The study offers practical implications for the development of culturally sensitive psychoeducational and spiritual counselling programmes aimed at supporting the mental health of religious professionals exposed to grief and death-related stressors.
Keywords: T & uuml;rkiye; Muslim religious officials; Death attitudes; Depression; Structural equation modelling